2015
DOI: 10.1037/h0100354
|View full text |Cite
|
Sign up to set email alerts
|

Event-related neural response to emotional picture stimuli following sleep deprivation.

Abstract: The impact of sleep deprivation on various stages of information processing was investigated during a valance categorization picture task using temporally sensitive event-related potentials (ERPs). Young, healthy, good sleepers were randomly assigned to a total sleep deprivation (n ϭ 22) or sleep control group (n ϭ 23). Picture stimuli were presented at random for 1000 ms and rated as very-positive, slightly positive, slightly negative, or very-negative. ERP measures included a parietal-occipital positive peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…This finding corroborates the literature identifying regulation as a buffer rather than an outcome of sleep (Cote et al, 2015; Schwarz et al, 2013). It is also the first study, to our knowledge, showing that emotion regulation use alters ties between sleep and inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding corroborates the literature identifying regulation as a buffer rather than an outcome of sleep (Cote et al, 2015; Schwarz et al, 2013). It is also the first study, to our knowledge, showing that emotion regulation use alters ties between sleep and inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, some studies suggest that a person’s emotion regulation strategies remain unchanged after sleep loss and, therefore, protect against its negative consequences. For example, after sleep restriction, people who frequently used cognitive reappraisal paid less attention to negative-emotion faces than did infrequent reappraisers (Cote et al, 2015). Because regulation strategies directly affect interpersonal communication, conflict, and intimacy between partners (Laurenceau et al, 2005), the question of whether they are reduced by or buffer the effects of short sleep is important; the two hypotheses have not been tested together in a single sample.…”
Section: Introductionmentioning
confidence: 99%
“…Neural evidence of this dysregulation indicates both an increased emotional reactivity and decreased cognitive control of the emotional reaction towards positive and negative affective stimuli (Gujar, Yoo, Hu, & Walker, 2011;Yoo, Gujar, Hu, Jolesz, & Walker, 2007). This emotional dysregulation has been further supported by behavioural findings of impulsivity (Anderson & Platten, 2011), increased attention towards negative stimuli (Cote, Jancsar, & Hunt, 2015), increased negativity towards neutral stimuli (Tempesta et al, 2010), less decrease in emotional response (Van Der Helm et al, 2011) and higher distractibility by negative images during working memory performance (Chuah et al, 2010) following sleep deprivation. Sleep deprivation has also been found to increase neural activity in reward networks when presented with positive pictures (Gujar et al, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…In addition, recent studies have also found a modulation effect of sleep deprivation on the 300-800 ms LPP but with mixed results (Alfarra et al, 2015;Cote et al, 2015). One study reported that LPP towards nonemotional stimuli increased after sleep deprivation but not towards emotional stimuli (Alfarra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep has a close relationship with emotional functioning and emotional health. Sleep loss has been found to impact various emotional functioning at subjective or behavioral levels (for reviews, see Beattie et al, 2015 andWatling et al, 2016), including mood states (Short & Louca, 2015), perception of emotional stimuli, such as pictures of emotional scenes (Daniela et al, 2010;Cote et al, 2015) and human facial emotions (van der Helm et al, 2010;Cote et al, 2014), emotional impulsivity (Anderson & Platten, 2011), emotional expressiveness (Minkel et al, 2011), and emotional intelligence (Killgore et al, 2008). In addition, at the neural level, an increasing number of studies consistently observed decreased functional connectivity within the brain network of prefrontal cortex (PFC)/anterior cingulate cortex (ACC) and subcortical limbic structures in response to emotional stimuli after sleep deprivation (Yoo et al, 2007;Gujar et al, 2011;Chuah et al, 2010;Simon et al, 2015), suggesting global deficits of monitoring and regulatory control of emotional functioning without sleep (Palmer & Alfano, 2017).…”
Section: Introductionmentioning
confidence: 99%